Nonlinear observability, identifiability, and persistent trajectories - Diop, S.; Fliess, M. (IEEE Decision and Control, 1991, 1991)
The concept of nonlinear observability and the theory of identifiability are discussed. The linear nature of the concept of observability is underlined. It is shown that a minimal realization should be defined only by its observability, which corroborates recent works on linear systems. This theory is applied to the related problem of identifiability. The concept of persistent trajectories is defined. Differential algebra is the main tool of this investigation.< >